Social Influence And Savings Behavior: Evidence From A Developing Country Context - Mpaata, Eva; Koskei, Naomy; Saina, Ernest (SEISENSE Journal of Management, 2020)
Purpose: This paper highlights the relevance of Savings Behavior and the impact of Social Influence on Savings Behavior in a developing country utilizing both life cycle and economic theories Methodology: This paper presents findings from a thorough review of the literature. Relevant articles were reviewed on both savings behavior and social influence. The articles consisted of both contexts developed versus developing. Findings: The findings suggest that from the developed country context, Social Influence positively affects Savings Behavior, which is not the case for the developing economies that show the negative impact of social influence on savings behavior. Therefore, financial education and literacy training are two of the means of encouraging individual self-control in these developing economies despite their vulnerability to social influence to encourage positive savings behavior. Implications: Individuals are encouraged to save, especially during their productive ages, along with their lifespan. This can be done by obligatory deductions for those that are officially employed. Originality/Value: This paper reveals a bibliography theoretical review on Social Influence and Savings Behavior within the developing country context. The paper presents the puzzle about the effect of Social Influence and Savings Behavior in the emerging economy. The majority of savings behavior research undertaken in the developed economies shows the positive effect of social influence on savings behavior, which is not the case in the developing economies.